Intelligent workloads at the edge : deliver cyber-physical outcomes with data and machine learning using AWS IoT Greengrass /: deliver cyber-physical outcomes with data and machine learning using AWS IoT Greengrass. (2022) - Mitra, Indraneel; Burke, Ryan
No abstract available